2003
DOI: 10.1099/vir.0.19532-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability of hepatitis A virus

Abstract: Knowledge of the molecular biology of hepatitis A virus (HAV) has increased exponentially since its identification. HAV exploits all known mechanisms of genetic variation to ensure survival, including mutation and genetic recombination. HAV has been characterized by the emergence of different genotypes, three human antigenic variants and only one major serotype. This paper reviews the genetic variability and molecular epidemiology of HAV. Its evolutionary mechanisms are described with particular emphasis on ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
106
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(113 citation statements)
references
References 114 publications
4
106
0
3
Order By: Relevance
“…Despite some degree of nucleotide heterogeneity at the P1 genomic region (4,11,22,35,43), there is not an equivalent degree of variation at the amino acid level (20,23,38). It has recently been demonstrated that HAV replicates as complex dynamic mutant distributions or quasispecies (37).…”
mentioning
confidence: 99%
“…Despite some degree of nucleotide heterogeneity at the P1 genomic region (4,11,22,35,43), there is not an equivalent degree of variation at the amino acid level (20,23,38). It has recently been demonstrated that HAV replicates as complex dynamic mutant distributions or quasispecies (37).…”
mentioning
confidence: 99%
“…When these are defined by sequence variation within the VP1/P2A junction, there is 15% nucleotide variation between isolates and 7 to 7.5% nucleotide variation between subgenotypes. Of the 6 HAV genotypes identified thus far, 3 (genotypes I, II, and III) are of human origin, and 3 (genotypes IV, V, and VI) are of simian origin (2,4,6,7,19,33).…”
mentioning
confidence: 99%
“…Genotype I, II, and III are associated with human infection, while genotype IV, V, and VI are found in simians [27]. A genotype VII, designated SLF88, was proposed in an earlier study [24], but further analysis of the complete genome and capsid region of additional strains indicated that the genotype VII should be reclassified as genotype IIB [25,26]. Genotype I and III can be each further divided into subgenotypes IA, IB, IIIA, and IIIB.…”
Section: Hav Genome and Genotypesmentioning
confidence: 99%
“…HAV displays a high level of antigenic conservation throughout the viral genome. An immunological study identified the existence of a single human serotype of HAV [23], but ample genetic diversity still exists to classify HAV into six genotypes based upon differences of a 186-bp nucleotide sequence in the VP1-P2A junction region [24][25][26]. Genotype I, II, and III are associated with human infection, while genotype IV, V, and VI are found in simians [27].…”
Section: Hav Genome and Genotypesmentioning
confidence: 99%